2021
DOI: 10.3389/fimmu.2021.634402
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan-Induced IL-10 Secretion by Monocytes Triggers Porcine NK Cell Cytotoxicity

Abstract: Beta-glucans are naturally occurring polysaccharides present in cell walls of fungi, yeast, bacteria, cereals, seaweed, and algae. These microbe-associated molecular patterns (MAMPs) possess immunomodulatory properties. In human, it has been suggested that NK cells can be activated by β-glucans. Here, we aimed to elucidate whether β-glucans modulate porcine NK cell responses in vitro and if so, how these effects are mediated. We investigated the effect of two β-glucans, Macrogard and Curdlan, which differ in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In this study, our data suggested that β-glucan induces IL-10 expression and reduces virus-induced lung pathological inflammation in experimental animals. In addition, a recent study reported that β-glucan enhances NK cell killing activity by promoting IL-10 secretion by porcine monocytes [33], which suggests that IL-10 indirectly regulates NK killing function and improves antiviral effects. However, β-glucan inhibition of virus-infected lung injury may involve multiple mechanisms, and this protective mechanism will be revealed using gene deletion animal models in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our data suggested that β-glucan induces IL-10 expression and reduces virus-induced lung pathological inflammation in experimental animals. In addition, a recent study reported that β-glucan enhances NK cell killing activity by promoting IL-10 secretion by porcine monocytes [33], which suggests that IL-10 indirectly regulates NK killing function and improves antiviral effects. However, β-glucan inhibition of virus-infected lung injury may involve multiple mechanisms, and this protective mechanism will be revealed using gene deletion animal models in the future.…”
Section: Discussionmentioning
confidence: 99%
“…multiple days are performed in a basal medium containing rhIL-15 to assure NK cell viability (60). In however, rpIL-15 is not sufficient retain satisfying viability in NK cells and TGF-b treatment was therefore combined with either IL-2 or IL-10, cytokines that are able to maintain porcine cNK cell viability (61,62). In line with a report in human (58), IL-10 nor TGF-b were able to increase Eomes expression in porcine cNK cells, but TGF-b was able to downregulate T-bet expression in these cells.…”
Section: Indications For (Partial) In Vitro Plasticity From Cnk Cells...mentioning
confidence: 99%
“…Natural killer cells (NK cells) are extremely important immune cells in the body, which are naturally occurring non-specific immune killer cells in the organism and play a crucial role in intracellular immune processes against parasitic infections, tumours and viruses, and have both immunomodulatory and cytotoxic functions. In an in vitro experiment to investigate how Fermentum β-polysaccharide activates porcine NK cells, the addition of β-polysaccharide to porcine NK cells triggered the release of cytokines TNF-α, IL-6 and IL-10 from peripheral blood mononuclear cells ( Hermans et al, 2021 ). Increased NK cytotoxicity can mediate the killing of tumour cells and virus-infected cells, thus enhancing the non-specific immune function of the body.…”
Section: Activitymentioning
confidence: 99%